Q: Skills for Success : Listening and Speaking - Scanlon, Jaimie (Oxford University Press, 2011)
Books is a series of six levels with two sections, Reading and Writing and Listening and Speaking. The set provides students: Well-defined learning outcomes keep students focused on their lesson goals. Thought-provoking questions provide a framework for critical thinking for each unit. Clear communication skills help students improve their language skills. All practice activities and new content per unit, approximately 20 hours of practice per series using Q Online